Effect of dietary lignocellulose on ileal and total tract digestibility of fat and fatty acids in broiler chickens. Issue 6 (14th April 2016) - Bogusławska‐Tryk, M.; Piotrowska, A.; Szymeczko, R.; Burlikowska, K.
Summary: The study was conducted to determine the effect of a lignocellulose supplemented diet on apparent ileal and total tract digestibility of fat and fatty acids (FA) in broiler chickens. A total of 48 21‐day‐old male Ross 308 chickens were divided into four treatment groups ( n  = 12) with six replicates per treatment. From 21 to 42 days of age, the broilers were fed experimental diets varied in the amount of lignocellulose: 0%, 0.25%, 0.5% and 1%. Total excreta were gathered during the last 3 days of the feeding trial and digesta was collected from the ileum at 42 days of the bird age. Digestibility was determined by the indicator method. The ether extract content in diet/digesta/excreta was determined by the gravimetric method, and fatty acid methyl esters were analysed by gas chromatography–mass spectrometry. Fat digestibility measured to the end of the small intestine and in the whole gastrointestinal tract in birds was high and exceeded 90% and 87% respectively. Addition of lignocellulose (1%) increased (p < 0.05) ileal fat digestibility but had no significant effect on total tract fat digestion. Absorption of total fatty acids (TFA) as well as myristic (C14:0), palmitoleic (C16:1) and α‐linolenic (C18:3 n −3) acids, estimated by both methods, was significantly higher in birds fed the diets supplemented with lignocellulose, especially at a dose of 1%. Total tract absorption of some dietary polyunsaturated fatty acids (PUFA) (C20:2, C20:4 n −6) was significantly lower from diet supplemented with 0.5% and 0.25% lignocellulose. There was observed a decrease in apparent digestibility of fat and most examined fatty acids, when measured between terminal ileum and total gastrointestinal tract. The results suggest that lignocellulose can affect digestion and FA absorption in broilers but, as the effect of lignocellulose was not studied previously, further investigations are necessary to confirm the results of the present experiment.